From pathogenesis to new developments in treatment of primary progressive multiple sclerosis. Literature review - A. Juknelytė; Ž. Vaičekauskytė; D. Mickevičienė; R. Balnytė (Neurologijos seminarai)
Multiple sclerosis (MS) is characterised as a chronic autoimmune inflammatory disease of the central nervous system (CNS) affecting more than 2.3 million people all over the world. Approximately 15% of all MS cases are manifesting as primary progressive MS (PPMS). Inflammation has long been thought to be the initial factor that starts pathological mechanisms, and neurodegeneration only enhances the progression of the disease. Recent data reveal more precise details about the pathogenesis of PPMS that led to the development of a new drug. After years of failed treatment methods, the new drug Ocrelizumab has shown promising results in the treatment of PPMS. The drug was approved in 2018 by the European Medicines Agency (EMA). Considered an incurable disease, PPMS today gives patients more hope of stopping the progression of disability.